2012
DOI: 10.1007/s10750-012-1319-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of light attenuation in large rivers of the Amazon

Abstract: The light field and its relationship with biogeochemical variables were investigated in the Solimões, Negro, Amazon, Madeira, Uatumã, Trombetas, and Tapajós Rivers. In high suspended sediment rivers, total suspended matter is the primary control on light attenuation (r = 0.8), with colored dissolved organic matter (CDOM) being secondary (r = -0.6) due to scattering and absorption, respectively. Photosynthetically active radiation was the lowest (\100.0 lmol m -2 s -1 at the depth of half Z 1% ) and was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…On the other hand, impacted rivers, such as the Crepori (Class 4) and the Tocantins (Class 3), showed Z m /Z c of~2.0 during the high water level period, which suggests a reduction of light availability to half of the water column. Analogous restriction of light availability has been reported in the Amazon River and it is associated with the low chl-a concentration given that nutrients are not limited in these waters [24,32,50,56].…”
Section: Underwater Light Field and Phytoplanktonmentioning
confidence: 65%
See 3 more Smart Citations
“…On the other hand, impacted rivers, such as the Crepori (Class 4) and the Tocantins (Class 3), showed Z m /Z c of~2.0 during the high water level period, which suggests a reduction of light availability to half of the water column. Analogous restriction of light availability has been reported in the Amazon River and it is associated with the low chl-a concentration given that nutrients are not limited in these waters [24,32,50,56].…”
Section: Underwater Light Field and Phytoplanktonmentioning
confidence: 65%
“…In the Tapajós, for example Costa et al [32] observed, on average, lower acdom absorption (acdom (440) = 3.2 m −1 ) than values measured in black water rivers of the Amazon (8.6 m −1 ). As a result of the low TSS and acdom, the diffuse attenuation coefficient (Kd PAR) was reported at around 2.0 m −1 in both rising and falling periods, whereas for black and white Amazonian rivers, Kd increases to 3.7 and 5.1 m −1 , respectively [32].…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Gymnotiforms inhabit the Amazon and Orinoco drainage basins where short-wavelength light is attenuated; depending on water clarity and the presence of particulates or phytoplankton, green-red or red light transmits best [Costa et al, 2013]. Despite the loss of SWS1 and SWS2 cone opsins and the lack of green cones, the retention of LWS cones assures the gymnotiform retina will be optimally sensitive to the dominant light spectrum in their habitat during the daytime.…”
Section: Gymnotiforms Retain the Optimal Cone Opsin For Their Habitatmentioning
confidence: 99%